2011
DOI: 10.1245/s10434-011-2092-6
|View full text |Cite
|
Sign up to set email alerts
|

Is Focused Minimally Invasive Parathyroidectomy Appropriate for Patients With Familial Primary Hyperparathyroidism?

Abstract: The vast majority of patients who underwent a MIP were surgically cured. Although recurrence rates remain higher in the familial hyperparathyroidism group, these data suggest that this alone should not be a contraindication to MIP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 25 publications
1
6
1
Order By: Relevance
“…One major drawback of SPTX and TPTX, however, is their reported high rate of permanent postoperative hypoparathyroidism of up to 66% (Table ), which was also the case in the present study with 32% after TPTX and 17% after SPTX, respectively. All patients after TPTX developed a transient postoperative hypoparathyroidism requiring substitution therapy.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…One major drawback of SPTX and TPTX, however, is their reported high rate of permanent postoperative hypoparathyroidism of up to 66% (Table ), which was also the case in the present study with 32% after TPTX and 17% after SPTX, respectively. All patients after TPTX developed a transient postoperative hypoparathyroidism requiring substitution therapy.…”
Section: Discussionsupporting
confidence: 76%
“…Therefore, recent practice guidelines previously recommended SPTX or TPTX as procedures of choice for this condition, since rates of recurrence and postoperative hypoparathyroidism rates were acceptable during short‐term follow‐up (Table ). In the literature, the recurrence rate after TPTX varies between 0% and 60% compared with 4.4% in the present study. Some authors preferring TPTX report lower recurrence and disease persistence rates compared with SPTX .…”
Section: Discussioncontrasting
confidence: 48%
See 2 more Smart Citations
“…Trans-cervical thymectomy is usually performed, during both these procedures, to prevent thymic carcinoid and remove possible ectopic parathyroid glands ( 5 ). However, some reports have shown that limited excision of the affected parathyroid glands could obtain the same result in correcting the hypercalcemia, with a lower risk of persistent hypoparathyroidism ( 6 8 ).…”
Section: Introductionmentioning
confidence: 99%